2021
DOI: 10.1002/cssc.202100182
|View full text |Cite
|
Sign up to set email alerts
|

Aromaticity/Antiaromaticity Effect on Activity of Transition Metal Macrocyclic Complexes towards Electrocatalytic Oxygen Reduction

Abstract: The effect of the coordination sphere around metal centers on the oxygen reduction reaction (ORR) activity of transition metal macrocyclic complexes is still unclear. Here, the aromaticity/antiaromaticity effect of macrocycles on ORR activity was investigated based on TM norcorrole (TM=Mn, Fe, Co, Ni), TM porphycene, and TM porphyrin by first‐principle calculations. It was found that the complexes with weaker aromatic macrocycles exhibited a stronger adsorption strength while the complexes with antiaromatic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…The PISO analysis shows a relatively weak π bonding interaction between the 5MR and the terminal carbon in the radical when the corresponding original form species is highly aromatic. Note that previous reports have shown that antiaromaticity helps improve the adsorption strength of transition-metal macrocyclic complexes toward electrocatalytic oxygen reduction and also promotes dihydrogen activation . In this work, we have demonstrated that the antiaromaticity contributes to the formation of thermodynamically more stable radicals through DFT calculations, in line with the experimental study by Winter’s group very recently .…”
Section: Discussionsupporting
confidence: 89%
“…The PISO analysis shows a relatively weak π bonding interaction between the 5MR and the terminal carbon in the radical when the corresponding original form species is highly aromatic. Note that previous reports have shown that antiaromaticity helps improve the adsorption strength of transition-metal macrocyclic complexes toward electrocatalytic oxygen reduction and also promotes dihydrogen activation . In this work, we have demonstrated that the antiaromaticity contributes to the formation of thermodynamically more stable radicals through DFT calculations, in line with the experimental study by Winter’s group very recently .…”
Section: Discussionsupporting
confidence: 89%
“…As a result, performance of Ni-L2 on ORR is improved but that of Fe-L2 and Co-L2 are inhibited. ΔG(∗OOH) of Ni-L2 system decreases from 0.95 eV to 0.71 eV at an external potential of 1.23 V. Previous study demonstrated that the complexes with antiaromatic macrocycles significantly enhance adsorption strengths, mainly because of the various redox activities of macrocyclic ligands with different aromaticities ( Ni et al., 2021 ). The antiaromatic ligand is more likely to accept electrons to become a stable state.…”
Section: Resultsmentioning
confidence: 98%
“…Ni et al. computationally investigated the relationship between the aromaticity/antiaromaticity of the macrocycles and the activity of transition metal centered complexes as ORR electrocatalysts ( Ni et al., 2021 ). The antiaromatic macrocyclic ligand can enhance adsorption strength with oxygenated intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…Macrocyclic chemistry provides fascinating strategies [4] to formulate a chemical design involving metals and ligands in the form of macrocyclic complexes for chemical, biological, therapeutic, and electrochemical applications [5,6]. Due to their structural diversity and potential applications in electrochemistry, macrocyclic complexes have attracted a great deal of attention following chemical modi cations [7]. This includes substitution in the molecular framework and the replacement of core metal ions.…”
Section: Introductionmentioning
confidence: 99%